PENGEMBANGAN PERANGKAT PEMBELAJARAN BERDASARKAN PEMBELAJARAN BERBASIS MASALAH UNTUK MENINGKATKAN KEMAMPUAN PENALARAN MATEMATIK - Rosmita Sari Siregar (JURNAL MATHEMATIC PAEDAGOGIC, 2019)
This research aim to : (1) To analyse validity of study peripheral base on the problem based learning which have been developed to improve the ability of mathematical reasoning, (2) To analyse effectiveness of study peripheral base on the problem based learning which have been developed to improve the ability of mathematical reasoning, (3) To analyse the improvement of ability mathematical reasoning student by using study peripheral base on the problem based learning which have been developed.. Research type used is development research by using modification of development model 4-D. This Research step is define, design, develop and disseminate. In this research is compiled by peripheral of study and instrument that is : lesson plan, sheet of student activity, teacher book, student book, tes of ability of reasoning. Try out conducted atstudent of class VIII-A as much 23 people and VII-B as much 25 people in MTS. Cerdas Murni Medan. Result of this research indicate that : (1) Validity of study peripheral of according to expert team is valid (2) Study Peripheral reach the effective criterion that is complete of klasikal reach 91,3%, respon student to study obtained mean 95,02% and study time not differ far with the ordinary study time, (3) Improvement the ability of mathematical reasoning use the study peripheral base on the problem which have been developed to be seen from value N-Gain that is 0,61 in category "medium"Keyword :   Development of Study Peripheral, Problem Based Learning, Mathematic Reasoning,